Chocolate and Lipstick: Gender (Re)construction in Dancing Docs and Dandies - Gilbert, Reid (Studies in Canadian Literature, 1995)
Identity in physical theatre is constructed: the performers construct identity through the physical art form, and meaning is carried within these constructions. Dancing Docs and Dandies, a performance art company working on the Fringe circuit in 1995, tackles literary conventions and gender stereotypes; the two dancers, Cooke and Lott, (re)construct their bodies through manipulation of art and audience participation. This construction of identity opens new and useful avenues of exploration for drama critics.